The Question of Baltic States in the Policy of the Great Westem Powers in 1944-1945 - Ramojus Kraujelis (Lietuvos Istorijos Studijos)
The considerations of the three Great powers in the final years (1944-1945) of World War II and the question of the Baltic states within the context of international relations and diplomacy of these powers are discussed in the article.